1994
DOI: 10.1007/bf00192476
|View full text |Cite
|
Sign up to set email alerts
|

Primary lymphoma of bone

Abstract: A survey of the 2075 cases in the Leeds Bone Tumour Registry showed that 54 cases of Primary Lymphoma of Bone that had been registered since data collection began in 1958 (2.6% of primary bone tumours). The overall sex ratio was 1.5 males: 1 female, largely due to the preponderance of males in the under 40 age group. The age distribution was bimodal, the second peak of incidence demonstrating a significant reversal of the sex ratio with females being more commonly affected in the older group. The clinical feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
3
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 6 publications
0
42
3
3
Order By: Relevance
“…Previous studies have reported that the pelvis and/or femur are the most commonly presenting sites of PBL (2,8,9,15,(17)(18)(19)(20). In contrast, the spine (41.6%) was the most common primary site in our study.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Previous studies have reported that the pelvis and/or femur are the most commonly presenting sites of PBL (2,8,9,15,(17)(18)(19)(20). In contrast, the spine (41.6%) was the most common primary site in our study.…”
Section: Discussioncontrasting
confidence: 49%
“…Primary bone lymphoma (PBL) is a rare manifestation of non-Hodgkin lymphoma (NHL), accounting for less than 1% of all cases of malignant lymphoma and 3% of malignant bone tumors (1)(2)(3). Diffuse large B-cell lymphoma (DLBCL) is the most common pathological type of this rare disorder, representing over 80% of cases of primary bony NHL (1).…”
Section: Introductionmentioning
confidence: 99%
“…Primary bone lymphoma is a rare disease, accounting for about 3% of all primary bone malignancies, <5% of extranodal lymphomas and 1-2% of all lymphomas in adults (Limb et al, 1994;Fletcher, 2006;Maruyama et al, 2007;Ramadan et al, 2007;Jawad et al, 2010). This lymphoma arises more often in the femur, spine, and pelvic bones, but,…”
Section: Discussionmentioning
confidence: 99%
“…Two MB-DLBCL patients (5Á4%) with spine and skull involvement experienced central nervous system (CNS) relapse. Thus, MB-DLBCL patients exhibit a significantly better prognosis compared to patients with advanced-stage DLBCL, and should be treated with conventional anthracycline-based chemotherapy, keeping intensified treatment for relapsing cases, considering involved-field radiotherapy, and CNS prophylaxis in high-risk patients.Keywords: primary bone lymphoma, polyostotic lymphoma, osteolymphoma, multifocal bone lymphoma.Primary bone lymphoma is a rare disease, accounting for about 3% of all primary bone malignancies, <5% of extranodal lymphomas and 1-2% of all lymphomas in adults (Limb et al, 1994;Fletcher, 2006;Maruyama et al, 2007;Ramadan et al, 2007;Jawad et al, 2010). This lymphoma arises more often in the femur, spine, and pelvic bones, but,…”
mentioning
confidence: 99%
“…It represents 3% of all primary bone malignancies, <2% of all adult lymphomas, and 5% of extranodal lymphomas [2][3][4][5]. Diffuse large B-cell lymphoma accounts for approximately 80% of cases [3,4].…”
mentioning
confidence: 99%